The Role of Horizontal Communication in Minimizing Product Defects within the Manufacturing Painting Process - Muhamad Kamaludin; Koesworo Setiawan; Ruhimat Ruhimat (Journal of Innovative and Creativity (Joecy), 2026)
This study addresses the vital role of consistent product quality in manufacturing, which heavily relies on operators' understanding of quality standards. This study aims to analyze the effectiveness of horizontal communication in distributing paint quality standard information at PT Kandakawana Sakti. The descriptive qualitative method was employed, utilizing in-depth interviews with quality control heads, foremen, and spray operators for data collection. Scientific findings revealed that the primary barriers to information distribution stemmed from abstract qualitative terminology and shifting parameter inconsistencies between work shifts. However, the implementation of tactical two-way communication proved highly effective in minimizing technical misunderstandings. Through optimizing visual media, enforcing concrete numerical instructions, and fostering instant feedback on the production floor, horizontal coordination successfully reduced paint defect (reject) rates from 8–10% to 3–4% per month. In conclusion, an adaptive, responsive, and structured horizontal communication channel plays a crucial role in maintaining smooth fabrication workflows and ensuring consistent quality in manufacturing products.